HUBUNGAN FAKTOR SOSIAL, EKONOMI DAN DEMOGRAFI DALAM KEIKUTSERTAAN KELUARGA BERENCANA DI DESA YOSOWILANGUN KIDUL KABUPATEN LUMAJANG TAHUN 2023 - Erfanda Puspita; Nova Hikmawati; Farianingsih Farianingsih (NHM PRESS, 2023)
Contraceptives are drugs or tools to delay or space out pregnancies,and stop fertility. This study aimed to analyze the relationship between social, economic and demographic factors in family planning participation.The research method used descriptive-analytic using the cross-sectional approach. The Population in Yosowilangun Kidul Village with participants who do not use contaception is 45 people. The sample used for this study was 30 people.The research results were obtained from 30 respondents, namely from social, economic, and demographic factors as much as 16.7% had good social, economic, and demographic factors.The conclusion is that there is a relationship between social, economic, and demographic factors in planning family participation.Suggestions are providing counseling to the public about contraception so that people are willing to use family planning, providing information to the public that there is a family planning program, especially Family Planning Safari (cooperation between family planning program coordinators). As well as empowering cadres to disseminate information to the public. Before choosing contraception,midwives should conduct counseling so that they understand the advantages and disadvantages of contraception. For other researchers, this is so that they can develop research designs and variables to be studied.Examine more deeply the variables that influence family planning participation.Due to the results of this study, there were only 3 related variables that were studied.